2016
DOI: 10.3233/web-160348
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent recommender system based on predictive analysis in telehealthcare environment

Abstract: Abstract. The use of intelligent technologies for providing useful recommendations to patients suffering chronic diseases may play a positive role in improving the general life quality of patients and help reduce the workload and cost involved in their daily healthcare. The objective of this study is to develop an intelligent recommender system based on predictive analysis for advising patients in the telehealth environment concerning whether they need to take the body test one day in advance by analyzing medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…However, in the context of HF, limited studies apply predictive models. Lafta et al [24] is one of these studies that using several telemonitored attributes (i.e., heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and oxygen saturation) applied basic time series prediction algorithm, regression-based time series prediction algorithm, and hybrid time series prediction algorithm. e obtained results showed that up to 75% and 98% of accuracy values could be obtained across different patients under three algorithms, but still the accuracy value is not objective enough to determine how well the system performs.…”
Section: Predictive Models On Telemedicine Systemsmentioning
confidence: 99%
“…However, in the context of HF, limited studies apply predictive models. Lafta et al [24] is one of these studies that using several telemonitored attributes (i.e., heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and oxygen saturation) applied basic time series prediction algorithm, regression-based time series prediction algorithm, and hybrid time series prediction algorithm. e obtained results showed that up to 75% and 98% of accuracy values could be obtained across different patients under three algorithms, but still the accuracy value is not objective enough to determine how well the system performs.…”
Section: Predictive Models On Telemedicine Systemsmentioning
confidence: 99%
“…For the success of the recommender system, it is very important to choose what type of criteria are used to evaluate the recommender system. Conventionally, recommender systems were evaluated based on criteria borrowed from information retrieval [9,31,36]. Common metrics used in the evaluation are:…”
Section: Evaluation Of Hrsmentioning
confidence: 99%
“…The increasing amount of data available to medical professionals for diagnosing diseases and developing treatment plans for their patients raise the importance of having suitable tools to harness such data and transform them into meaningful information. Such tools are also useful for evidence-based decision making within the healthcare domain [14]. Health-care professionals can no longer solely rely on pen and paper as more and more data are in digital form.…”
Section: Introductionmentioning
confidence: 99%